Paclitaxel-Loaded PBCA Nanoparticles for Targeted Drug Delivery in Ovarian Cancer - Ghahremani, Hamid; Ourang, Zahra; Izadidehkordi, Shadi; Zandi, Sara; Ebadi, Mehdi; Ebrahimzade, Mohammadreza (Asian Pacific Journal of Cancer Biology, 2025)
Overview: Resistance to paclitaxel remains a critical barrier in the effective treatment of ovarian cancer, often resulting in reduced clinical responses and increased recurrence rates. Nanoparticle-mediated drug delivery has emerged as a promising strategy to overcome such resistance by enhancing drug bioavailability and targeting tumor cells more precisely. The present study focuses on the formulation of poly(butyl cyanoacrylate) (PBCA) nanoparticles to facilitate controlled paclitaxel delivery and improve its therapeutic efficacy against drug-resistant ovarian cancer cells. Methods: Paclitaxel-loaded PBCA nanoparticles were synthesized using a mini-emulsion polymerization technique. Physicochemical properties were assessed by measuring hydrodynamic size, polydispersity index (PDI), zeta potential, and in vitro drug release behavior. Morphological evaluation was conducted via Scanning Electron Microscopy (SEM) to confirm particle uniformity and surface characteristics. Cytotoxicity was examined against the A2780CIS ovarian cancer cell line following 48 hours of exposure to the nanoformulation and free paclitaxel. Results: The formulated nanoparticles displayed a spherical morphology with an average diameter of 355 nm, a PDI of 0.29, and a surface charge of –18.4 mV. Drug release profiling demonstrated a sustained and controlled release, with approximately 42% of paclitaxel released over 40 hours under physiological conditions. Cellular viability assays revealed that treatment with paclitaxel-loaded PBCA nanoparticles led to a 68% reduction in cell viability, significantly outperforming free paclitaxel, which showed a 41% decrease under identical conditions (p < 0.01). Conclusion: PBCA nanoparticles exhibited favorable physicochemical characteristics and enhanced anticancer activity in paclitaxel-resistant ovarian cancer cells. These findings support their potential application as a targeted and efficient nanocarrier system for improving the therapeutic index of chemotherapeutic agents in drug-refractory malignancies.